RASIONALITAS AFEKTIF DAN PANGGUNG DEPAN DIGITAL: STUDI SOSIOLOGIS PERILAKU KONSUMTIF MAHASISWA TERHADAP BUDAYA DISKON DI E-COMMERCE - Fatin Zulfa Fadhilah; Dinda Agustina; Desinta Anggoro Pangesty (Yayasan Literasi Sains Indonesia, 2025)
E-commerce is one example of the development of digital technology today. The existence of e-commerce facilitates the buying and selling of goods and services. Students are one example of a social group that is prone to consumptive behavior. This study analyzes the factors behind the causes of consumptive behavior among students using sociological theories from Max Weber and Erving Goffman. The research method used is qualitative research using secondary data related to consumptive behavior and e-commerce. The results show that, from Max Weber's perspective, consumptive behavior influenced by discounts is explained by the background of students' consumptive behavior through affective, traditional, and instrumental rationality. Meanwhile, Erving Goffman's perspective explains that students' consumptive behavior is influenced by the symbolic interactionism of digital e-commerce technology in terms of colors, icons, and notifications, which implicitly cause students to open them significantly. Discounts not only function as an economic strategy but also as a social symbol that influences students' consumptive behavior. The results of this study identified several factors that may occur and efforts to prevent them. For that further research can examine other factors and subjects more broadly in order to obtain a more comprehensive understanding of all aspects.